Kajian Sistematis Efek Anti-oksidan Terapi Akupunktur pada Berbagai Penyakit - Andry Hartanto; Dwi Surya Supriyana; Ario Imandiri; Willie Japaries; Suminah Suminah; Yelini Fan Hardi (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Background: Homeostasis is a key concept in life survival. Today, researchers are discovering redox homeostasis as the basis of a wide variety of degenerative diseases. Various methods are studied to maintain redox homeostasis, especially by increasing the body's antioxidant defenses, so that they can prevent and treat various modern diseases, one of which is through acupuncture. Methodology: This article is a systematic review of the therapeutic effects of acupuncture on redox homeostasis published in the PubMed database, Researchgate, CNKI, in the last 10 years. Results: The concept of redox homeostasis is identical to that of Yin-Yang homeostasis in TCM (traditional Chinese medicine). It turns out that acupuncture therapy, which has the effect of maintaining and restoring Yin-Yang homeostasis, has also been shown to have an effect on increasing antioxidant power and reducing body oxidants in various pathological conditions. There are no adverse effects from acupuncture therapy. Conclusion: Acupuncture therapy is effective and safe for maintaining and restoring redox homeostasis, especially for its anti-oxidant effect in various redox reward conditions.